2022
DOI: 10.3390/ijms23169459
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ubiquitome Analysis Reveals Deubiquitinating Effects Induced by Wolbachia Infection in Drosophila melanogaster

Abstract: The endosymbiotic Wolbachia bacteria frequently cause cytoplasmic incompatibility (CI) in their insect hosts, where Wolbachia-infected males cross with uninfected females, leading to no or fewer progenies, indicating a paternal modification by Wolbachia. Recent studies have identified a Wolbachia protein, CidB, containing a DUB (deubiquitylating enzyme) domain, which can be loaded into host sperm nuclei and involved in CI, though the DUB activity is not necessary for CI in Drosophila melanogaster. To investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…The infection, distribution of Wolbachia and its ability to manipulate the reproductive properties of arthropod hosts have attracted much interest concerning its role in the host’s biology, ecology, and evolution, as well as in the development of novel, symbiont based and environmentally friendly based methods for pest and disease management ( Bourtzis and Miller, 2006 ; Hedges et al., 2008 ; Moreira et al., 2009 ; Laidoudi et al., 2020 ; Ilinsky et al., 2022 ; Zong et al., 2022 ). For instance, recent studies have shown that, the presence of Wolbachia in some insect species may provide antiviral protection, and inhibit the infection and transmission of certain pathogens such as Dengue, Zika, Chikungunya, Yellow fever, Mayaro viruses and rice ragged stunt virus (RRSV) ( Moreira et al., 2009 ; Walker et al., 2011 ; Van den Hurk et al., 2012 ; Frentiu et al., 2014 ; Tan et al., 2017 ; Ryan et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The infection, distribution of Wolbachia and its ability to manipulate the reproductive properties of arthropod hosts have attracted much interest concerning its role in the host’s biology, ecology, and evolution, as well as in the development of novel, symbiont based and environmentally friendly based methods for pest and disease management ( Bourtzis and Miller, 2006 ; Hedges et al., 2008 ; Moreira et al., 2009 ; Laidoudi et al., 2020 ; Ilinsky et al., 2022 ; Zong et al., 2022 ). For instance, recent studies have shown that, the presence of Wolbachia in some insect species may provide antiviral protection, and inhibit the infection and transmission of certain pathogens such as Dengue, Zika, Chikungunya, Yellow fever, Mayaro viruses and rice ragged stunt virus (RRSV) ( Moreira et al., 2009 ; Walker et al., 2011 ; Van den Hurk et al., 2012 ; Frentiu et al., 2014 ; Tan et al., 2017 ; Ryan et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%